2006
DOI: 10.1210/jc.2005-2168
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Acylated Ghrelin during Oral Glucose Tolerance Test Is Correlated with Whole-Body Insulin Sensitivity in Children with Prader-Willi Syndrome

Abstract: Our results suggest that AG is sensitively suppressed by insulin and that this suppression correlated with insulin sensitivity in PWS children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 35 publications
9
31
1
Order By: Relevance
“…Despite overall higher levels of ghrelin in PWS, these subjects still exhibited normal postprandial suppression of ghrelin in our study, consistent with results reported in 3 studies of children with PWS (Haqq et al, 2003, Paik et al, 2006and Paik et al, 2007b and another of adults (Gimenez-Palop et al, 2007). Future trials are needed to elucidate the role of ghrelin in PWS using specific ghrelin antagonists, currently in development.…”
Section: Discussionsupporting
confidence: 90%
“…Despite overall higher levels of ghrelin in PWS, these subjects still exhibited normal postprandial suppression of ghrelin in our study, consistent with results reported in 3 studies of children with PWS (Haqq et al, 2003, Paik et al, 2006and Paik et al, 2007b and another of adults (Gimenez-Palop et al, 2007). Future trials are needed to elucidate the role of ghrelin in PWS using specific ghrelin antagonists, currently in development.…”
Section: Discussionsupporting
confidence: 90%
“…26,27,32,34,36 --38,40,43 --48 Levels of ghrelin do fall after food intake in children and adults with PWS but remain elevated compared with the controls relative to their obesity. 37,38,40,43,44 In our current study, we were unable to demonstrate any elevation of plasma ghrelin levels in PWS children under 5 years, unadjusted or when correcting for age, BMI, fasting insulin or insulin resistance. This finding is in agreement with previous studies of PWS children aged under 3 or 5 years, 39,42,46 although it should be noted that one of these studies did not find hyperghrelinaemia in PWS children over 3 years and adults either.…”
Section: Ghrelincontrasting
confidence: 80%
“…39,42,46 Furthermore, hyperghrelinaemia in older children and PWS adults may be partially, though not solely, explained by preserved insulin sensitivity and relative hypoinsulinaemia, as ghrelin levels are negatively correlated with insulin. 29,34,38,40,46,47 Ghrelin levels also rise with starvation and weight loss. 18,20 Thus, differences between studies might also depend on differences in the dynamic nutritional state, body composition and insulin status.…”
Section: Ghrelinmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the correlation between the effects of DAG infusion on postprandial glycemia and baseline AG levels before the start of the meal in the SBM protocol warrants further study, as it suggests the clinical benefits of DAG administration in subjects with relatively high levels of AG. Appropriate subjects to study might be those with Prader-Willi syndrome (PWS), who not only are hyperphagic and morbidly obese but have elevated ghrelin levels (18,19). This shows that there may be a suppressive (or upregulating) controlling mechanism of ghrelin secretion in PWS children.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%